ANALISIS KEKUATAN BENDING MATERIAL ABS (ACRYLONITRILE BUTADIENE STYRENE) PRODUK 3D PRINTING - Ashari Ramadhan (2024)
3D printing is a printing technology in the modern digital age. In the industrial world, this technology is also referred to as rapid prototyping technology. Rapid prototyping is a technology that combines modern technology, for example, when you want to carry out the manufacturing process, a drafter is needed, and a drafter needs a CAD / CAE-based design software. ABS material is the most commonly used material. In addition to its low price, this material is strong and and recyclable. Acrylonitrile butadiene styrene is a filament widely used in 3D printing. However, it is most commonly used for injection molding and extrusion. This research process uses ABS material on three-dimensional prints. The parameter scenarios are nozzle speed, nozzle temperature, and nozzle diameter. Specimen modeling using the help of fusion 360 software according to ASTM D955 standardization for use in the 3-point bending testing process. The specimen test results obtained that the parameters in 3D printing are very important, especially the use of nozzle parameters. The results of this study provide data that 3D printing parameters affect different values for each specimen, such as width, height, span length, maximum load, bending strength. The results of testing bending strength data of 51.4 Mpa to 79.4 Mpa, and bending elasticity modulus data of 1549.7 Mpa to 3311 Mpa. ABS material has good toughness, because to achieve fractures in the material requires a fracture stress value of almost 80 Mpa. Good nozzle parameter variation from average values, namely (temperature 235 °C, diameter 0.6 mm, speed 30 mm / s).